MODEL DASHBOARD INFORMASI KEUANGAN MAHASISWA TERINTEGRASI REST API SEBAGAI PENUNJANG PENGAMBILAN KEPUTUSAN DI UNIVERSITAS FALETEHAN - Edi Suherlan; Aufa Dhia Ghaisani Suherlan; Iqbal Fernando (Journal of Innovation And Future Technology, 2025)
Universitas Faletehan faces challenges in managing student financial data due to the lack of integration between the BNI e-collection system and the university’s internal academic information system. This study aims to design a web-based student financial dashboard model utilizing REST API technology to automate data exchange between the bank’s server and the academic system. The development process adopts the ADDIE model, combined with a prototyping approach and User-Centered Design (UCD) principles. The resulting dashboard provides real-time and integrated financial transaction data, improving reporting efficiency and supporting strategic decision-making by university leaders. Additionally, it enhances transparency, accountability, and contributes to the digital transformation of financial management in higher education institutions.The main result indicates that access to financial data improved significantly, reducing reporting delays from batch-based (24+ hours) to under 5 seconds, with 85% of users reporting high satisfaction.